A text analysis and gatekeepers' perspectives of a promotional genre: Understanding the rhetoric of Fulbright grant statements. (October 2020) - Kessler, Matt
Abstract: This study investigates the rhetorical strategies of successful applicants to the Fulbright English Teaching Assistant (ETA) grants program. Using a move-step analysis, I analyzed 50 personal statements and 50 statements of grant purpose written by applicants between 2012 and 2016. Also incorporated are six Fulbright faculty-raters' views of these statements through think-alouds and semi-structured interviews. Findings suggest successful ETA applicants utilize four moves in their personal statements: (1) competence claims, (2) motivation for pursuing ETA grant, (3) motivation for applying to target country, and (4) framing childhood and family history . In applicants' statements of grant purpose, most writers again utilize three moves from the personal statements (1–3). Faculty-raters' perspectives are discussed in relation to the moves-steps the raters find influential, and also, raters' perspectives concerning the ideal rhetoric of/relationship between personal statements and statements of grant purpose. Implications are discussed for future grant applicants and related genres such as graduate school applications. Highlights: The rhetoric of a promotional genre is explored using a corpus of 100 Fulbright EFL-teaching grant applications. Each application included a personal statement and a statement of grant purpose. Six target grant raters' perspectives are included through think-aloud protocols and semi-structured interviews. The results highlight the difficulties novice writers face in working with occluded genres. Pedagogical implications are discussed for the Fulbright grant and related genres such as graduate school applications.